Knowledge and compliance with Good Manufacturing Practices at the Simoca - Tucumán fair. 2018 - Rodríguez, Eliana M. (2020)
Introduction: Good Manufacturing Practices (GMP) are practices and procedures, their application is mandatory for establishments that produce, handle and sell food. Compliance with them avoids Foodborne Diseases (ETAS) guaranteeing health. The sale of food on public roads is a traditional practice, it represents a risk when GMPs are not applied. The objectives were to evaluate knowledge about GMP, investigate the application, and analyze the relationship between knowledge and the application of GMP. Methods: descriptive-correlational, cross-sectional study. The sample consisted of 20 individuals in charge of the 20 stalls at the Simoca Fair, with prior informed consent. The information was collected through a previous pilot test survey and a checklist in 2018. Results: People between 20 and 29 years of age, with complete primary and secondary education, predominated. Regarding the degree of knowledge about BPM, 65% presented a high degree of knowledge, while the remaining 35% a medium degree. With respect to the implementation of the BPM, it was determined that all of them do not apply. No relationship was found between the degree of knowledge and application of them, the high degree of knowledge is not reflected in compliance with the GMP. Conclusion: The need for training, greater controls and evaluations for the application of the GMP is evident, since they would avoid the ETAS.